2010
DOI: 10.1097/rlu.0b013e3181db4ce9
|View full text |Cite
|
Sign up to set email alerts
|

F-18 FDG PET/CT Imaging in Small Cell Prostate Cancer

Abstract: Positron emission tomography/computed tomography scan with F-18 fluorodeoxyglucose was performed in a 77-year-old patient with prostatic adenocarcinoma treated with hormonal therapy, who presented 2 years later with an abdominal mass and slowly increasing prostate specific antigen and carcinoembryonic antigen. Positron emission tomography-computed tomography scan showed intense uptake of F-18 fluorodeoxyglucose in the prostate tumor, iliac, and periaortic lymph nodes and also in a focal area in the right lobe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The Warburg effect, initially described in 1924, has received renewed attention recently in the field of cancer metabolism due to the widespread clinical application of Fluorodeoxyglucose (FDG) – Positron Emission Tomography (PET) imaging which is based on increased glucose uptake by cancer cells. Unlike most tumors, however, FDG-PET imaging cannot detect localized, untreated PCa 5 , but can image SCNC 6 , suggesting that metabolic differences may be an underlying mechanism for the vastly different biologic behaviors of AdenoCa and SCNC. Additionally, literature has shown that prostatic AdenoCa utilizes mitochondrial respiration which is unique to the metabolism displayed in other tumor cells 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The Warburg effect, initially described in 1924, has received renewed attention recently in the field of cancer metabolism due to the widespread clinical application of Fluorodeoxyglucose (FDG) – Positron Emission Tomography (PET) imaging which is based on increased glucose uptake by cancer cells. Unlike most tumors, however, FDG-PET imaging cannot detect localized, untreated PCa 5 , but can image SCNC 6 , suggesting that metabolic differences may be an underlying mechanism for the vastly different biologic behaviors of AdenoCa and SCNC. Additionally, literature has shown that prostatic AdenoCa utilizes mitochondrial respiration which is unique to the metabolism displayed in other tumor cells 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Small cell prostate carcinoma (SCPC) is a rare, aggressive form of prostate cancer with a poor prognosis, comprising approximately 0.5% to 1% of all prostate cancers. 1 Median survival in patients with SCPC is 12 months. 2,3 Small cell prostate carcinoma is commonly diagnosed in the setting of clinical progression of PCA patients on long-term androgen deprivation therapy.…”
Section: Figurementioning
confidence: 99%
“…This resulted in the higher rate of glucose uptake and lactate production in presence of oxygen (Vander Heiden et al, 2009 ). Early clinical studies have shown that fluorodeoxyglucose (FDG)-PET imaging which is based on increased glucose uptake by cancer cells failed to detect naïve localized PCa (Effert et al, 1996 ), but can detect the advanced stage small cell prostate cancer (SCPC) (de Carvalho Flamini et al, 2010 ), highlighting the metabolic differences underlying the adenocarcinoma and SCPC. Moreover, the higher uptake of glucose has been associated with the elevated expression of Glucose Transporter 1 (GLUT1) in poorly differentiated hormone-independent PCa (Effert et al, 2004 ).…”
Section: Factors Governing Cellular Plasticitymentioning
confidence: 99%